Pengaruh Getaran dan Kebisingan terhadap Kesehatan Awak Kapal dan Ekosistem Laut" - ASA, ABRILIA (Blueprint Journal, 2025)
The maritime industry plays an important role in supporting global trade.However, behind its strategic role, ship operations also have impacts that cannot be ignored, both on the health of the crew and on marine life.This research aims to gain a deeper understanding of how the vibrations and noise generated by ships affect the physical and mental conditions of the crew, as well as their impact on marine life.The research was conducted through the measurement of vibration and noise levels on various types of ships, accompanied by a survey on the health and well-being of the crew.The results show that long-term exposure to vibrations can cause disturbances in muscles and bones, increase stress, and disrupt sleep quality.On the other hand, the underwater noise generated by ships has been proven to disrupt the communication abilities and migration patterns of marine mammals, as well as affect the reproductive processes of fish.These findings underscore the importance of awareness regarding the environmental impact of maritime activities, as well as the need for strategies to reduce vibrations and noise to create a healthier working environment for crew members and to maintain the sustainability of marine ecosystems.